2021
DOI: 10.3390/jrfm14110537
|View full text |Cite
|
Sign up to set email alerts
|

Can Sustainable Corporate Governance Enhance Internal Audit Function? Evidence from Omani Public Listed Companies

Abstract: With the application of the agency theory and institutional theory, this study is intended towards the measurement of sustainable corporate governance (SCG) impact on internal audit function (IA) within Omani public listed companies. This study will also theoretically consider the Chinese investment in Oman and its potential impact on Oman’s corporate governance. For this study, SCG is an independent variable and IA is the dependent variable. This study used a descriptive cross-sectional survey design. Data is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…This promotes the accountability and transparency of institutions. The IA literature used agency theory to explore areas such as external auditor reliance and IAFs (Al-Sukker et al, 2018), IAFs and internal control quality (Oussii & Boulila Taktak, 2018a), the role of sustainable CG in activating IAFs (Rehman, 2021), IA and financial performance (Hazaea, Tabash et al, 2021), and ACs effectiveness and banks’ performance (Y. A. Al-Matari et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This promotes the accountability and transparency of institutions. The IA literature used agency theory to explore areas such as external auditor reliance and IAFs (Al-Sukker et al, 2018), IAFs and internal control quality (Oussii & Boulila Taktak, 2018a), the role of sustainable CG in activating IAFs (Rehman, 2021), IA and financial performance (Hazaea, Tabash et al, 2021), and ACs effectiveness and banks’ performance (Y. A. Al-Matari et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have significantly enhanced our knowledge of the IA quality determinants, and several factors enhancing it have been identified. It has been suggested that the IA quality can be enhanced by the Big 4 auditors and ACs activities (Khlif & Samaha, 2016; Oussii & Boulila Taktak, 2018b; Sartawe et al, 2017), the management support (Alzeban & Gwilliam, 2014), electronic business management (Bshayreh et al, 2019), the objectivity and professionalism (Matarneh, 2011), culture and individualism (Alzeban, 2015), the level of compliance toward ethical rules (Alsmairat et al, 2018), sustainable CG (Rehman, 2021), and access to information (Krichene & Baklouti, 2021). The IA quality and its determinants appeared to be the most explored topic with 21 research articles (see Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They indicated that increasing investor protection strengthens CG and improves company performance. Nevertheless, no studies have focused on investors and companies in Yemen and revealed the CG factors that investors look at when making investment decisions (Mihail and Dumitrescu 2021;Gennaro and Nietlispach 2021;Choi et al 2020;Rehman 2021).…”
Section: Corporate Governance and Investmentmentioning
confidence: 99%
“…Internal control systems, corporate governance, and the performance of financial institutions are instrumental in having strong internal control systems (Rehman, 2021). The internal control system will be taken to represent all the approved policies and procedures used by the management in order to achieve effective management of the business.…”
Section: Introductionmentioning
confidence: 99%